2016
DOI: 10.1128/jvi.00161-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adeno-Associated Virus 1 and 6 Sialic Acid Binding Site

Abstract: The adeno-associated viruses (AAVs), which are being developed as gene delivery vectors, display differential cell surface glycan binding and subsequent tissue tropisms. For AAV serotype 1 (AAV1), the first viral vector approved as a gene therapy treatment, and its closely related AAV6, sialic acid (SIA) serves as their primary cellular surface receptor. Toward characterizing the SIA binding site(s), the structure of the AAV1-SIA complex was determined by X-ray crystallography to 3.0 Å. Density consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 77 publications
1
76
0
Order By: Relevance
“…Specifically, AAV1 requires sialylated glycans for cell surface attachment, which in turn determines transduction efficiency (23). The SA-binding site of AAV1 was resolved recently, revealing specific contact residues located in a pocket at the base of the threefold protrusions similar to the galactose binding site on AAV9 (16). Specific residues located within the SA binding pocket include S268, D270, N271, N447, S472, V473, N500, T502, and W503.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, AAV1 requires sialylated glycans for cell surface attachment, which in turn determines transduction efficiency (23). The SA-binding site of AAV1 was resolved recently, revealing specific contact residues located in a pocket at the base of the threefold protrusions similar to the galactose binding site on AAV9 (16). Specific residues located within the SA binding pocket include S268, D270, N271, N447, S472, V473, N500, T502, and W503.…”
Section: Discussionmentioning
confidence: 99%
“…Here we tested this hypothesis using AAV1 as a template, which we chose because of the availability of extensive structural information pertaining to this capsid complexed with different mAbs and its cognate glycan receptor, sialic acid (SA) (9,10,16). We then combined structural information from cryo-EM images of AAV1 capsids complexed with three different murine mAbs and directed evolution without selective pressure from NAbs to generate antibodyevading AAV variants.…”
mentioning
confidence: 99%
“…Although we did not pursue further the molecular underpinnings for this phenomenon, some inferences may be made based on the already existing literature. Several studies found that AAV1 and AAV6, which have structurally similar (∼99% homologous) capsid proteins, use α2,3 and α2,6 N -linked sialic acid moieties of the cell surface proteoglycans for entry (Wu et al, 2006c; Huang et al, 2016). In the present work, we found a strong dissimilarity between rAAV1 and rAAV6 in terms of their efficacy to transduce primary rat astrocytes in cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…GAGs are long unbranched polysaccharides composed of repeating disaccharide units of sulfated uronic acid and glucosamine residues (Figure 4c), and includes heparan sulfate (HS). Specific recognition of GAGs for cell attachment have been implicated for a number of non-enveloped icosahedral viruses such as human papillomavirus (HPV), belonging to Papovaviridae [48]; human parvovirus and adeno-associated viruses (AAV), belonging to Parvovirida e [9,49]; and enveloped icosahedral viruses such as Zika virus, Dengue virus and West Nile virus, belonging to Flaviviridae [50]. Although structural studies have provided general features of how these viruses interact with the negatively-charged HS, detailed understanding of the rules of glycan engagement is limited due to lack of atomic-level characterization of glycan interactions.…”
Section: Recognition Of Gags By Virusesmentioning
confidence: 99%